A novel gelatin-guided mesoporous bowknot-like Co3O4 anode material for high-performance lithium-ion batteries. Issue 11 (23rd February 2017) - Du, Haoran; Yuan, Chao; Huang, Kuangfu; Wang, Wenhai; Zhang, Kai; Geng, Baoyou
Abstract : A bowknot-like Co3 O4 material has been synthesized via a gelatin-assisted hydrothermal method, which exhibits superior cyclic stability and improved rate capability. Abstract : A mesoporous bowknot-like Co3 O4 material has been synthesized through a facile hydrothermal method, using cobalt nitrate as the cobalt source, urea as the precipitator and gelatin as the guide agent, followed by calcination at 600 °C in air. Morphology characterization reveals that this bowknot-like Co3 O4 material possesses a mesoporous structure consisting of nanoparticles. Electrochemical experiments illustrate that the mesoporous bowknot-like Co3 O4 anode material exhibits a superior first and 100th reversible specific capacity of 1427.9 mA h g −1 and 1388.8 mA h g −1 at 0.2C, respectively. This material also delivers a high charge capacity of 751.3 mA h g −1 after 150 cycles at 2C. The novel preparation method and satisfactory performance make the bowknot-like Co3 O4 a good candidate as a high-performance anode material for use in Lithium-Ion Batteries (LIBs).